The Effect of a Period of Kinesiotherapy and Reflexology on Pain Intensity and Range of Motion in Elderly Women With Knee Osteoarthritis - Fatemeh Kiani Dooghabadi; Nahid Khoshraftar Yazdi; Hossein Farzaneh (Biyumikānīk-i varzishī)
Objective: The aim of this study was to compare the effect of a period of therapeutic exercise and reflexology on pain intensity and range of motion in elderly women with knee osteoarthritis. Methods: 45 elderly women with osteoarthritis of the knee were purposefully selected and randomly divided into three groups of 15: therapeutic exercise, reflexology and control. The therapeutic exercise and reflexology group practiced therapy and reflexology for 4 weeks and 5 sessions per week. The control group also performed their daily activities. To assess the intensity of pain and the range of motion of the subjectchr('39')s knee, the visual pain scale VAS and goniometer were used in pre-test and post-test, respectively. Data analysis was performed by one-way analysis of variance and Tukeychr('39')s Post Hoc test. Results: The results showed that both types of therapeutic exercise protocol and reflexology have positive and significant effects on reducing pain intensity and increasing range of motion of the knee joint of the subjects (P≤0.05), and the therapeutic exercise protocol compared to the protocol. Reflexology had more significant effects on the rate of increase in range of motion (P=0.001; P=0.001, respectively). Conclusion: Based on the results, the use of both protocols of therapeutic exercise and reflexology is recommended to reduce the severity of pain and increase the range of motion of elderly women with osteoarthritis of the knee. Simultaneous use of these two protocols for treatment and greater effectiveness in this group of patients is recommended